THE TWO-STATE SOLUTION: IS IT STILL FEASIBLE? - Sofia Maria Tagliabue (European Scientific Journal, ESJ, 2014)
Many scholars and politicians have been advocating the end of the two-state solution, given major obstacles like the right of return for the refugees, the settlements, the weakness of the Palestinian state, security and borders. However, this paper argues that the everlasting stalemate in the Israeli-Palestinian peace process is not necessarily caused by problems concerning the two-state solution per se, but it is rather the result of psychological factors such as internal divisions, conflicting stances, lack of trust, and bad timing. Among all these obstacles to peace, the most influential impediment has been Israel’s behavior and unwillingness to compromise during the negotiations. In fact, the Israeli stance and rhetoric, and especially its continuous appropriation of land, have been very problematic, as they have not left space for genuine negotiations and real compromise. In this light, the two-state solution, as well as any other solution to end the stalemate, is not currently feasible, and it will never be unless there is a real change in the Israeli position.